Development of an audio and computer cognitive behavioral therapy for depression in older adults. (2nd August 2020) - Morthland, Martin; Shah, Avani; Meadows, James T.; Scogin, Forrest
Abstract: Background: The purpose of this paper is to discuss the development of two novel technology-based interventions for depression in older adults while comparing older adults' preferences for audio-based and computer-based cognitive behavioral therapy for depressive symptoms. The audio program consisted of eight compact discs and a workbook while the computer program consisted of 11 modules of similar duration provided on a tablet PC. Both interventions consisted of the following topics: 1) introduction, 2) identifying and changing unhelpful thoughts, 3) addressing feelings, 4) relaxation, 5) engaging in pleasant events, 6) assertiveness, and 7) problem-solving. Methods : Fifty-one older adults were recruited from medical settings and rural communities and randomly assigned to an immediate treatment group (computer or audio) with minimal contact or a four-week minimal contact delayed treatment control condition. Results: Participants rated computer-based and audio-based cognitive behavioral therapy fairly equally, with 75% of those who received audio treatment and 85% of those who received computer-based treatment indicating benefits to their mood. Discussion : Computer-based or audio-based cognitive behavioral treatments may be valuable, low-cost modalities to deliver psychotherapy to older adults with depressive symptoms within a health care setting. Both modalities seem to be accepted by older adults.